2008
DOI: 10.1063/1.2884343
|View full text |Cite
|
Sign up to set email alerts
|

Near-resonant energy transfer from highly vibrationally excited OH to N2

Abstract: The probability per collision P͑T͒ of near-resonant vibration-to-vibration energy transfer ͑ET͒ of one quantum of vibrational energy from vibrational levels = 8 and = 9 of OH to N 2 ͑ =0͒, OH͑͒ +N 2 ͑0͒ → OH͑ −1͒ +N 2 ͑1͒, is calculated in the 100-350 K temperature range. These processes represent important steps in a model that explains the enhanced 4.3 m emission from CO 2 in the nocturnal mesosphere. The calculated energy transfer is mediated by weak long-range dipole-quadrupole interaction. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
4
17
0
Order By: Relevance
“…Using two different potential energy surfaces, Shalashilin et al [1992] obtained values of 4.91 × 10 −13 cm 3 s −1 and 1.10 × 10 −12 cm 3 s −1 for the rate constant of the OH( υ = 9) + N 2 vibrational‐to‐vibrational energy exchange at room temperature. Burtt and Sharma [2008b] performed calculations employing second order perturbation theory and a standard dipole moment function. Both studies show relatively good agreement at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using two different potential energy surfaces, Shalashilin et al [1992] obtained values of 4.91 × 10 −13 cm 3 s −1 and 1.10 × 10 −12 cm 3 s −1 for the rate constant of the OH( υ = 9) + N 2 vibrational‐to‐vibrational energy exchange at room temperature. Burtt and Sharma [2008b] performed calculations employing second order perturbation theory and a standard dipole moment function. Both studies show relatively good agreement at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies show relatively good agreement at room temperature. Nevertheless, they predict a different temperature dependence; Shalashilin et al [1992] found that the rate constant decreases with increasing temperature, whereas Burtt and Sharma [2008b] predict an increase with increasing temperature. Future experiments should clarify which theoretical approach is the most predictive for this process.…”
Section: Discussionmentioning
confidence: 99%
“…They further exclude the sudden death mechanism as a possible deactivation scheme. There are also two theoretical studies (Shalashilin et al, 1995;Caridade et al, 2002) which investigated OH(ν) deactivation via O 2 , both supporting a combination of multiquantum and single-quantum quenching similar to the model of Adler-Golden (1997).…”
Section: Introductionmentioning
confidence: 64%
“…In earlier calculations 40,41 involving high vibrational levels of OH the authors postulated an increase in the gas kinetic diameter and hard sphere diameter with vibrational quantum number. This was necessitated by dramatic change in the rotational constant of OH and hence the bond distance with vibrational quantum number ͑rotational constant changes 42 from 17.84 cm −1 for v = 1 to 12.92 cm −1 for v =8͒.…”
Section: Discussionmentioning
confidence: 99%